EFEKTIVITAS MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) BERMUATAN ETNOMATEMATIKA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS: Array - Afriyani, Ade Novita; Purwaningsih, Dian (Jurnal Dialektika Program Studi Pendidikan Matematika, 2019)
This study aims to determine the effectiveness of the TGT learning model containing ethnomatics on students' mathematical problem solving abilities wake up flat side space (cubes & beams). Effectiveness can be seen from the level of completeness of students 'mathematical problem solving abilities, the comparison of students' mathematical problem solving abilities of the experimental class with the control class and the influence of students 'learning activities on students' mathematical problem solving abilities. The type of research in this study is quantitative research, with experimental research methods, and the approach used is the Posttest Control Group Design approach. The population in this study were eighth grade students of MTs Muhammadiyah Bumiayu. The sample used in this study is class VIII A as an experimental class and class VIII B as a control class. The method of sampling is the Cluster Sampling technique. Analysis of the data used are normality test, homogeneity test, completeness test, proposition completeness test, average difference test and simple regression test. The results of this study are the TGT learning model is loaded with effective ethnatics on students' mathematical problem solving abilities.